Anode catalyst, system and method for preparing glycolic acid from ethylene glycol by electrocatalysis
By growing metal hydroxide nanosheets on foam metal and loading palladium nanoparticles anode catalyst, the problem of easy poisoning and poor selectivity in electrocatalytic ethylene glycol oxidation is solved, and a high selectivity, high activity and long-term stable electrocatalytic reaction is achieved.
Patent Information
- Application Number
- CN202310011163.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-01-05
AI Technical Summary
The existing catalysts for electrocatalyzing the oxidation of ethylene glycol to prepare glycolic acid are easily poisoned by carbonyl intermediates, resulting in rapid deactivation of the catalyst, and the oxidation process is complex, poor selectivity, and high product separation cost.
An anode catalyst including foam metal and metal hydroxide nanosheets grown in situ on the foam metal are used, and the catalyst is supported by metal palladium nanoparticles, thereby improving the stability and selectivity of the catalyst by a specific preparation method.
Electrocatalytic ethylene glycol oxidation with high selectivity, high activity and long-term stability is achieved, and can operate at low voltage (1.15V) at industrial-grade current density. The selectivity of glycolic acid is as high as 91.6%, and the catalyst stability exceeds 200 hours, which is better than existing palladium-based catalysts.
Smart Images

Figure CN115992368B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical catalysis, and more specifically, to an anode catalyst and system for electrocatalytically preparing glycolic acid from ethylene glycol, and a method for electrocatalytically preparing glycolic acid from ethylene glycol. Background Art
[0002] Glycolic acid is an important organic synthesis intermediate and chemical product, widely used in organic synthesis, printing and dyeing, cosmetics, electroplating and petroleum industry. In recent years, glycolic acid has been widely used as a monomer in the synthesis of biodegradable plastics. At present, glycolic acid is mainly prepared by chemical synthesis or biosynthesis. Chemical synthesis requires strong acid / base medium and harsh reaction conditions (such as high temperature and high pressure), and there are problems such as poor selectivity and product decomposition or polymerization. The biological method of synthesizing glycolic acid is also a complex process. It uses hydroxyacetonitrile or ethylene glycol as raw materials and nitrile hydrolase or microbial hydrogenase as enzyme catalyst. It requires a long production cycle and a series of precise control of operating parameters, such as pH, precursor concentration and temperature. Therefore, it is of great significance to develop new and efficient strategies for the synthesis of glycolic acid.
[0003] Electrocatalytic synthesis of glycolic acid is a method of selectively oxidizing ethylene glycol to glycolic acid under the drive of electricity using a suitable electrocatalyst. To date, precious metal materials such as platinum and palladium are considered to be the best electrocatalysts for ethylene glycol oxidation. However, most platinum and palladium catalysts are currently easily poisoned by carbonyl intermediates (such as CO) generated during the reaction, resulting in their rapid deactivation within a few hundred seconds, which severely limits the industrial development of electrocatalytic synthesis of glycolic acid. In addition, since ethylene glycol oxidation involves a complex and uncontrollable oxidation process, including C1 and C2 pathways, the catalytic selectivity is poor and the product separation cost is high. Therefore, the development of electrocatalytic ethylene glycol oxidation systems and catalysts with high catalytic activity, high selectivity and high stability remains a research focus in this field. Summary of the invention
[0004] In view of the above background, the main object of the present invention is to provide an anode catalyst for preparing glycolic acid by electrolysis of ethylene glycol with high selectivity, high activity and long-term stability, and a system comprising the catalyst.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides an anode catalyst, which includes a foam metal and metal hydroxide nanosheets in-situ grown on the foam metal; the metal hydroxide nanosheets are loaded with metal palladium nanoparticles.
[0007] Preferably, in the anode catalyst, the mass density of the metal palladium nanoparticles and the metal hydroxide nanosheets is 1 to 5 mg / cm 2 It can be understood that the mass density refers to the sum of the mass of the metal palladium nanoparticles and the metal hydroxide nanosheets per square centimeter of the anode catalyst surface, which is 1 to 5 mg.
[0008] Illustratively, the particle size of the metal palladium nanoparticles is nanoscale, such as 50nm-800nm, 100nm-500nm, 200nm-400nm, etc.; the thickness of the metal hydroxide nanosheets is also nanoscale, such as 1nm-100nm, 2nm-50nm, 10nm-20nm, 3nm-10nm, etc.
[0009] Preferably, in the anode catalyst, the metal hydroxide nanosheets and the foam metal have the same metal element; the metal element is selected from any one of nickel, cobalt, iron and copper, more preferably nickel.
[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned anode catalyst, comprising the following steps:
[0011] The foamed metal is placed in hydrochloric acid for ultrasonic treatment, then cleaned and blown dry, and then placed in a chloropalladic acid aqueous solution and kept warm at 70-100° C. for 0.5-2 hours.
[0012] Preferably, the pH value of the chloropalladic acid aqueous solution is 7 to 8. The pH value of the chloropalladic acid aqueous solution may affect the formation of metal hydroxide nanosheets.
[0013] Preferably, the concentration of the chloropalladic acid aqueous solution is 1 to 15 mmol / L.
[0014] More preferably, after the heat preservation, a cleaning and drying step is further included: cleaning with deionized water for multiple times, then rinsing with ethanol, and finally placing in a vacuum drying oven at 60° C. to dry for 6 hours.
[0015] Exemplarily, the shape of the foam metal used can be selected as needed, and the foam metal is preferably a foam metal with a thickness of 0.5 to 2 mm.
[0016] Illustratively, the concentration of the hydrochloric acid is 1 to 3.0 mol / L.
[0017] Exemplarily, the ultrasonic treatment time is 30 min.
[0018] In a third aspect, the present invention provides a system for preparing glycolic acid from ethylene glycol by electrocatalysis, comprising: the above-mentioned anode catalyst, cathode catalyst and an alkaline electrolyte containing ethylene glycol.
[0019] The alkaline electrolyte containing ethylene glycol can be obtained by alkaline hydrolysis of PET plastic.
[0020] It can be understood that the system can be a three-electrode system or a two-electrode system. When it is a three-electrode system, it also includes a reference electrode, an anode electrolytic cell and a cathode electrolytic cell connected by a proton exchange membrane; the anode catalyst, the reference electrode, and the alkaline electrolyte containing ethylene glycol are located in the anode electrolytic cell, and the cathode catalyst, the reference electrode and the alkaline electrolyte are located in the cathode electrolytic cell.
[0021] Illustratively, the alkaline electrolyte is 1-5 mol / L potassium hydroxide or sodium hydroxide; in the alkaline electrolyte containing ethylene glycol, the concentration of ethylene glycol is 1-5 mol / L.
[0022] Exemplarily, the cathode catalyst may be selected from one of a carbon electrode, a platinum electrode, a glassy carbon electrode, a platinum carbon electrode and a platinum mesh electrode, more preferably a platinum electrode.
[0023] Exemplarily, the reference electrode can be selected and adjusted by those skilled in the art according to actual conditions, electrolysis requirements and product requirements. In order to better ensure the progress of the electrochemical reaction and thus improve the performance and efficiency of the electrolytic cell, the material of the reference electrode is preferably a mercury / mercury oxide reference electrode.
[0024] When it is a two-electrode system, the system also includes an anode electrolyzer and a cathode electrolyzer connected through a proton exchange membrane; wherein the anode catalyst and the alkaline electrolyte containing ethylene glycol are located in the anode electrolyzer, and the cathode catalyst and the alkaline electrolyte are located in the cathode electrolyzer.
[0025] Illustratively, the alkaline electrolyte is 1-5 mol / L potassium hydroxide or sodium hydroxide; in the alkaline electrolyte containing ethylene glycol, the concentration of ethylene glycol is 1-5 mol / L.
[0026] Preferably, the cathode catalyst is a foam metal loaded with metal phosphide nanosheets.
[0027] More preferably, in the cathode catalyst, the metal phosphide nanosheets and the foam metal have the same metal element; the metal element is selected from any one of nickel, cobalt, iron and copper.
[0028] Exemplarily, the method for preparing the cathode catalyst comprises the following steps:
[0029] The foamed metal is placed in an aqueous solution containing metal salt hydrate and urea, kept at 100-140°C for 8-15 hours, and then calcined with sodium hypophosphite in a protective atmosphere.
[0030] Preferably, the calcination is carried out by heating the temperature to 400-600°C at a rate of 2°C / min and keeping the temperature for 1-4h.
[0031] In a fourth aspect, the present invention provides a method for preparing glycolic acid from ethylene glycol by electrocatalysis, comprising the following steps: assembling any of the above systems into an electrolytic cell, applying voltage to carry out an electrocatalytic reaction, ethylene glycol is oxidized at the anode to generate glycolic acid, and water is reduced at the cathode to generate hydrogen.
[0032] It is understood that the use of the above-mentioned anode catalyst in the electrocatalytic production of glycolic acid from ethylene glycol is also within the scope of protection of the present invention.
[0033] Preferably, the voltage is in the range of 0.7 to 2.0V.
[0034] Preferably, after the electrocatalytic reaction, an operation of separating and purifying glycolic acid is also included, which specifically includes the following steps: decolorizing the electrolyzed solution with activated carbon, performing reduced pressure distillation and recrystallization.
[0035] Preferably, the recrystallization comprises the following steps: cooling the liquid after vacuum distillation to -20 to 0°C, adding glycolic acid seed crystals, maintaining the temperature and stirring for 12 to 24 hours, and vacuum drying to obtain glycolic acid crystals;
[0036] The amount of glycolic acid seed crystals added is 1 to 3 wt % of the glycolic acid contained in the liquid after reduced pressure distillation.
[0037] In addition, unless otherwise specified, any range described in the present invention includes the end value and any value between the end values and any sub-range formed by the end value or any value between the end values. The preparation methods in the present invention are conventional methods unless otherwise specified, the raw materials used can be obtained from public commercial channels or prepared according to the prior art unless otherwise specified, the percentages are mass percentages unless otherwise specified, and the solutions are aqueous solutions unless otherwise specified.
[0038] The beneficial effects of the present invention are as follows:
[0039] 1. The anode catalyst provided by the present invention can prepare glycolic acid with high selectivity, high activity and high stability. Specifically, when the industrial current density is reached (600 mA / cm 2 ), the operating voltage is only 1.15V; when the ethylene glycol conversion is 93.2%, the selectivity of glycolic acid is as high as 91.6%; in addition, the anode catalyst can achieve stable electrolysis for more than 200 hours, which is better than all current palladium-based ethylene glycol oxidation catalysts.
[0040] 2. The method for preparing glycolic acid from ethylene glycol by electrocatalysis provided by the present invention has a simple process, readily available raw materials, mild reaction conditions, and simple separation and purification operations; in addition, the method can also achieve multi-production with existing coal-to-ethylene glycol industrial equipment, which not only solves the overcapacity of ethylene glycol, but also is an effective supplement to the ethylene glycol industry chain. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0042] Figure 1 The appearance morphology of the nickel foam in Example 1 and the anode catalyst Pd-Ni(OH)2 / NF prepared in the experimental group is shown.
[0043] Figure 2 The XRD spectrum of the anode catalyst Pd-Ni(OH)2 / NF prepared in the experimental group of Example 1 is shown.
[0044] Figure 3 The Raman spectrum of the anode catalyst Pd-Ni(OH)2 / NF prepared in the experimental group of Example 1 is shown.
[0045] Figure 4 The SEM image of the anode catalyst Pd-Ni(OH)2 / NF prepared in the experimental group of Example 1 is shown.
[0046] Figure 5 The TEM image of the anode catalyst Pd-Ni(OH)2 / NF prepared in the experimental group of Example 1 is shown.
[0047] Figure 6 The EDS energy spectrum of the anode catalyst Pd-Ni(OH)2 / NF prepared in the experimental group of Example 1 is shown.
[0048] Figure 7 The appearance morphology of the cathode catalyst Ni2P / NF prepared in Example 2 is shown.
[0049] Figure 8 The SEM morphology of the cathode catalyst Ni2P / NF prepared in Example 2 is shown.
[0050] Fig. 9 The LSV curve diagram of water electrolysis and ethylene glycol electrolysis using Pd-Ni(OH)2 / NF as the anode in Example 3 is shown.
[0051] Fig.10The anolyte before and after electrolysis with Pd-Ni(OH)2 / NF as anode in Example 3 is shown. 1 H NMR spectrum.
[0052] Fig.11 The Faraday efficiency diagram of the anolyte of Example 3 with Pd-Ni(OH)2 / NF as the anode at different voltages is shown.
[0053] Fig.12 A schematic diagram of a flow electrolysis cell of Example 4 is shown; wherein a) is a physical diagram of the flow electrolysis cell, and b) is a schematic diagram of the structure of the flow electrolysis cell.
[0054] Fig.13 The it curve during the anolyte flow electrolysis process of Example 4 is shown.
[0055] Fig.14 The glycolic acid crystals obtained in Example 5 are shown 1 H NMR spectrum.
[0056] Fig.15 The glycolic acid crystals obtained in Example 5 are shown 13 C NMR spectrum.
[0057] Fig.16 The SEM image of the anode catalyst Pd-Ni(OH)2 / NFF-nanoparticles prepared in the control group of Example 1 is shown.
[0058] Fig.17 The LSV curves of the two anode catalysts prepared in Example 1 for electrolysis of ethylene glycol are shown. DETAILED DESCRIPTION
[0059] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention rather than limiting the patent claims of the present invention.
[0060] There is no particular limitation on the purity of all raw materials in the present invention, and analytical purity is preferably adopted in the present invention.
[0061] The sources and abbreviations of all raw materials in the present invention are conventional sources and abbreviations in the field, and are clear and definite in the field of their relevant uses. Those skilled in the art can purchase them from commercial sources or prepare them by conventional methods based on the abbreviations and corresponding uses.
[0062] The present invention has no particular limitation on the time of the electrocatalytic reaction. Those skilled in the art can 1The electrolysis product glycolic acid is qualitatively or quantitatively analyzed by H spectrum, gas chromatography, weighing method or XRD spectrum to determine the progress and completion time of the reaction.
[0063] The calculation method of conversion rate in the following examples is: conversion rate % = amount of reacted raw materials / total amount of original raw materials×100%.
[0064] Example 1: Preparation of anode catalyst
[0065] Experimental group: First, the nickel foam was cut into 1cm×3cm pieces, ultrasonically treated in 1.0mol / L hydrochloric acid for 30min, then ultrasonically cleaned in deionized water and ethanol for 3 times, and finally dried with a hair dryer for later use; the cleaned nickel foam was placed in a pre-prepared 10mL 5mmol / L chloropalladic acid aqueous solution (the pH was adjusted to 7 with sodium hydroxide in advance), and then placed in an oil bath that had been heated to 90℃. After keeping warm for 1h, the nickel foam, which originally had a bright metallic luster on the surface, turned black, as shown in Figure 2. Figure 1 As shown. The nickel foam was quickly taken out and washed with deionized water for several times, then rinsed with ethanol twice, and finally placed in a vacuum drying oven at 60°C for 6 hours. The final material was recorded as palladium-nickel hydroxide / nickel foam (Pd-Ni(OH)2 / NF), and the mass density of Pd-Ni(OH)2 was 1.5 mg / cm 2 .
[0066] Control group: Cut the nickel foam into 1cm×3cm, ultrasonically treat it in 1.0mol / L hydrochloric acid for 30min, then ultrasonically clean it in deionized water and ethanol for 3 times, and finally blow dry it with a hair dryer for use; put the cleaned nickel foam into a pre-prepared 10mL 5mmol / L chloropalladic acid aqueous solution (the pH was adjusted to 6 with sodium hydroxide in advance), and then put it into an oil bath that has been heated to 90°C and keep warm for 1h. Quickly take out the nickel foam, wash it with deionized water several times, rinse it with ethanol twice, and finally dry it in a vacuum drying oven at 60°C for 6h. The final material is recorded as palladium-nickel hydroxide / nickel foam-nanoparticles (Pd-Ni(OH)2 / NF-nanoparticles) (morphology see Fig.16 ).
[0067] from Figure 2 It can be seen that the material prepared by the experimental group in this case contains palladium crystal phase and nickel hydroxide crystal phase, indicating that Pd-Ni(OH)2 / NF was successfully prepared; Figure 3 The Raman spectrum also shows that the material prepared by the experimental group in this example contains palladium and nickel hydroxide; Figure 4 From the SEM spectrum, it can be seen that nickel hydroxide nanosheets grow vertically on nickel foam; Figure 5 From the TEM spectrum, it can be seen that the palladium nanoparticles are evenly distributed on the nickel hydroxide nanosheets; Figure 6 From the EDS spectrum, we can see that the material prepared by the experimental group mainly contains three elements: palladium, nickel and oxygen. Fig.16 It can be seen that in the materials prepared in the control group, palladium and nickel hydroxide are both nanoparticles distributed on the nickel foam.
[0068] Example 2: Preparation of cathode catalyst
[0069] First, cut the nickel foam into 1cm×3cm, ultrasonically treat it in 1.0mol / L hydrochloric acid for 30min, then ultrasonically clean it in deionized water and ethanol for 3 times, and finally blow it dry with a hair dryer for use; put the cleaned foam metal into 15mL of an aqueous solution containing 1mmol / L Ni(NO3)2·6H2O and 5-20mmol / L urea 10mmol / L, keep it in an oven at 120℃ for 12h, and after cooling to room temperature, take it out and wash it with deionized water and ethanol for several times, and then dry it in a vacuum drying oven; weigh 800mg of sodium hypophosphite and put it at one end of the porcelain boat, and put the above-treated nickel foam at the other end. Then transfer the porcelain boat to the middle part of the quartz tube, and finally install the quartz tube on the tube furnace and let the sodium hypophosphite be in the upwind position. After the device is built, open the argon valve and continuously flow argon gas in a small amount for protection. Finally, the temperature program of the tube furnace was set up: first, the temperature was increased by 2°C per minute, and the temperature was maintained for 2 hours after reaching 500°C, and finally the heating was stopped and the temperature was naturally cooled to room temperature. After taking it out, it was rinsed with deionized water several times, and finally put into a vacuum drying oven for drying. The final material was recorded as nickel phosphide / nickel foam (Ni2P / NF).
[0070] from Figure 7 It can be seen that the nickel foam, which originally had a bright metallic luster on the surface, turned black; Figure 8 The SEM image shows that nickel phosphide nanosheets grow vertically on nickel foam.
[0071] Example 3: Preparation of glycolic acid by electrolysis of ethylene glycol in a three-electrode H-type electrolytic cell
[0072] The anode catalyst prepared in the experimental group and the control group of Example 1 was used as the anode, the electrode working area was (0.5 cm×0.5 cm), Hg / HgO was used as the reference electrode, the Pt sheet was used as the cathode, and the electrode working area was (0.5 cm×0.5 cm). The anolyte was: 60 mL 1 mol / L potassium hydroxide + 1 mol / L ethylene glycol; the cathode electrolyte was: 60 mL 1 mol / L potassium hydroxide. The anode chamber and the cathode chamber were connected through a proton exchange membrane (Nafion 117) with a diameter of 2 cm, and the applied voltage was 0.7 to 2.0 V compared to the reversible hydrogen electrode.
[0073] Fig. 9The LSV curves of water electrolysis and ethylene glycol electrolysis with Pd-Ni(OH)2 / NF as anode are shown in the figure. It can be seen from the figure that when the current density reaches 100mA / cm 2 At this time, the voltage required for electrolysis of ethylene glycol is only 0.69V, which is much lower than the 1.65V required for electrolysis of water. When the current density reaches the industrial level of 600mA / cm 2 At that time, the voltage required for electrolysis of ethylene glycol was only 1.15V; Fig.10 The electrolyte before and after electrolysis with Pd-Ni(OH)2 / NF as anode 1 H NMR spectrum shows that after the electrolysis, ethylene glycol is almost completely converted into glycolic acid (ethylene glycol conversion rate is 93.2%, and GA selectivity is as high as 91.6%). Fig.11 The Faradaic efficiency diagram at different voltages with Pd-Ni(OH)2 / NF as the anode shows that the Faradaic efficiency is greater than 85% when electrolyzed at 0.7-1.2V relative to the reversible hydrogen electrode. Fig.17 : The LSV curves of electrolyzing ethylene glycol using Pd-Ni(OH)2 / NF-nanoparticles and Pd-Ni(OH)2 / NF as anodes, respectively. It can be seen from the figure that the anode catalyst containing nickel hydroxide nanosheets has better electrocatalytic performance.
[0074] Example 4: Preparation of glycolic acid by electrolysis of ethylene glycol using a two-electrode flow electrolysis cell
[0075] Pd-Ni(OH)2 / NF was used as the anode with an electrode working area of (3cm×3cm); Ni2P / NF was used as the cathode with an electrode working area of (3cm×3cm). The anolyte was 5mol / L potassium hydroxide + 1mol / L ethylene glycol flowing into the nickel-based anode electrolyzer at a flow rate of 0.15mL / min; the catholyte was 1mol / L potassium hydroxide flowing into the nickel-based cathode electrolyzer at a flow rate of 5mL / min. The nickel-based anode electrolyzer and the nickel-based cathode electrolyzer were connected through a 3.5cm×3.5cm proton exchange membrane (Nafion 117) (electrolysis device such as Fig.12 As shown), the applied voltage is 1.2V and the temperature is 50°C.
[0076] Fig.13 This is the it curve of electrolysis. It can be seen from the figure that the catalyst can achieve stable electrolysis for more than 200 hours, which is better than all current palladium-based ethylene glycol oxidation catalysts.
[0077] Example 5: Separation and purification of glycolic acid product
[0078] The reaction solution after electrolysis in Example 4 was first decolorized with activated carbon, and then neutralized with hydrochloric acid to a weak acidity (pH=5) to obtain a glycolic acid mixed solution; vacuum distillation (pressure of minus 0.1 MPa, temperature of 50°C) was performed to remove part of the water and concentrate the glycolic acid content to 65-85%; the concentrated solution was cooled to -5°C at 1°C / min, and then glycolic acid seed crystals were added in an amount of 2% of the glycolic acid content in the concentrated solution, and the temperature was further cooled to -15°C for recrystallization, and the temperature was maintained and stirred for 12-24 hours to completely precipitate glycolic acid crystals. Vacuum drying was performed to obtain glycolic acid crystals. Fig.14 Glycolic acid crystals 1 H NMR spectrum, Fig.15 Glycolic acid crystals 13 C NMR spectrum.
[0079] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. An anode catalyst for electrocatalytically preparing glycolic acid from ethylene glycol, characterized in that: It comprises a foam metal and a metal hydroxide nanosheet in-situ grown on the foam metal; the metal hydroxide nanosheet is loaded with metal palladium nanoparticles; The anode catalyst is prepared according to the following steps: The foamed metal is placed in hydrochloric acid for ultrasonic treatment, cleaned and blown dry, and then placed in a chloropalladic acid aqueous solution and kept at 70-100°C for 0.5-2h; The pH value of the chloropalladic acid aqueous solution is 7-8.
2. The anode catalyst according to claim 1, characterized in that In the anode catalyst, the mass density of the metal palladium nanoparticles and the metal hydroxide nanosheets is 1 to 5 mg / cm 2 .
3. The anode catalyst according to claim 1, characterized in that In the anode catalyst, the metal hydroxide nanosheets and the foam metal have the same metal element; the metal element is selected from any one of nickel, cobalt, iron and copper.
4. A method for preparing an anode catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: The foamed metal is placed in hydrochloric acid for ultrasonic treatment, cleaned and blown dry, and then placed in a chloropalladic acid aqueous solution and kept at 70-100°C for 0.5-2h; The pH value of the chloropalladic acid aqueous solution is 7-8.
5. The preparation method according to claim 4, characterized in that: The concentration of the chloropalladic acid aqueous solution is 1-15 mmol / L.
6. A system for preparing glycolic acid from ethylene glycol by electrocatalysis, characterized in that: include: An anode catalyst according to any one of claims 1 to 3 or an anode catalyst and a cathode catalyst prepared by the preparation method according to any one of claims 4 to 5, and an alkaline electrolyte containing ethylene glycol.
7. The system according to claim 6, characterized in that The cathode catalyst is a foam metal loaded with metal phosphide nanosheets.
8. The system according to claim 6, characterized in that In the cathode catalyst, the metal phosphide nanosheets and the foam metal have the same metal element; the metal element is selected from any one of nickel, cobalt, iron and copper.
9. A method for preparing glycolic acid from ethylene glycol by electrocatalysis, characterized in that: The method comprises the following steps: assembling the system described in any one of claims 6 to 8 into an electrolytic cell, applying voltage to carry out an electrocatalytic reaction, ethylene glycol is oxidized at the anode to generate glycolic acid, and water is reduced at the cathode to generate hydrogen.
10. The method according to claim 9, characterized in that The voltage is in the range of 0.7 to 2.0V.
11. The method according to claim 9, characterized in that After the electrocatalytic reaction, the process also includes the operation of separating and purifying glycolic acid, which specifically includes the following steps: decolorizing the electrolyzed solution with activated carbon, performing reduced pressure distillation and recrystallization.
12. The method according to claim 11, characterized in that The recrystallization comprises the following steps: cooling the liquid after vacuum distillation to -20 to 0°C, adding glycolic acid seed crystals, maintaining the temperature and stirring for 12 to 24 hours, and vacuum drying to obtain glycolic acid crystals; The amount of glycolic acid seed crystals added is 1 to 3 wt % of the glycolic acid contained in the liquid after reduced pressure distillation.
Citation Information
Patent Citations
Modified foamed nickel supported noble metal catalyst hydrogen evolution electrode and preparation method thereof
CN110438528A
Pd nanoparticle-loaded ferronickel double hydroxide nanosheet array structure material, preparation method and application thereof
CN111871426A